Modelling the impact of deep-water crustacean trawl fishery in the marine ecosystem off Portuguese Southwestern and South Coasts: I) the trophic web and trophic flows - Angeles Torres, Maria (2020)
The concentration of the population in coastal regions, in addition to the direct human use, is leading to an accelerated process of change and deterioration of the marine ecosystems. Human activities such as fishing together with environmental drivers (e.g. climate change) are triggering major threats to marine biodiversity, and impact directly the services they provide. In the South and Southwest coasts of Portugal, the deep-water crustacean trawl fishery is not exemption. This fishery is recognized to have large effects on a number of species while generating high rates of unwanted catches. However, taking into account an ecosystem-based perspective, the fishing impacts along the food web accounting for biological interactions between and among species caught remains poorly understood. These impacts are particularly troubling and are a cause of concern given the cascading effects that might arise. Facing the main policies and legislative instruments for the restoration and conservation of the marine environment, times are calling for implementing ecosystem-based approaches to fisheries management. To this end, we use a food web modelling (Ecopath with Ecosim) approach to assess the fishing impacts of this particular fishery on the marine ecosystem of southern and southwestern Portugal. In particular, we describe the food web structure and functioning, identify the main keystone species and/or groups, quantify the major trophic and energy flows, and ultimately assess the impact of fishing on the target species but also on the ecosystem by means of ecological and ecosystem-based indicators. Finally, we examine limitations and weaknesses of the model for potential improvements and future research directions.